2006
DOI: 10.1258/095646206775455694
|View full text |Cite
|
Sign up to set email alerts
|

Delivering results to clients: a question of satisfying needs or desires?

Abstract: Demand for genitourinary (GU) medicine services is outstripping supply. Improving efficiency can modulate the supply side of the equation, e.g. decreasing the number of clients having to return for their results. This survey explored how clients at two central London GU medicine clinics would like to receive their results and their views were reflected against what was offered by London GU medicine clinics. There was a significant difference between the result delivery services that the clients wanted and what… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 1 publication
0
11
0
Order By: Relevance
“…Even allowing for this, patients and potential patients expressed a clear preference to receive their results explicitly even if they were negative, which is in accordance with a previous report. 5 Although 'no news is good news' may free clinic resources, reduce costs and improve waiting times it remains generally unacceptable to patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Even allowing for this, patients and potential patients expressed a clear preference to receive their results explicitly even if they were negative, which is in accordance with a previous report. 5 Although 'no news is good news' may free clinic resources, reduce costs and improve waiting times it remains generally unacceptable to patients.…”
Section: Discussionmentioning
confidence: 99%
“…11 Patients views remain an important input to the design of sexual health-care services, 12 including the measurement of satisfaction with new initiatives. 5,13 This study obtained views from STI clinic patients and a community sample on alternative ways of providing results to patients, methods of partner notification and expectations on how long a clinic attendance for STI screening should last.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study highlighted a number of practical issues for conducting SRHH PPE, many of which have been found by other projects. These include the need to be innovative, provide training and information for participants, using mixed methods, in‐depth and personalized methods …”
Section: Discussionmentioning
confidence: 99%
“…Recent research has focused on what patients want 1,4 -6 and the introduction of newer technologies such as texting. 1,3,7 Not surprisingly, a paper in 2008 revealed that patients prefer the 'human touch', i.e. prefer telephone and face-to-face contact rather than the newer technologies.…”
Section: Introductionmentioning
confidence: 99%